Understanding health education, health promotion and public health - van Teijlingen, Kitty R.; Devkota, Bhimsen; Douglas, Flora; Simkhada, Padam; van Teijlingen, Edwin R. (Journal of Health Promotion, 2021)
Across the globe, there can be confusion about the difference between the concepts of health education, health promotion and, often also, public health. This confusion does not limit itself to the individual terms but also to how these terms relate to each other. Some use terms such as health education and health promotion interchangeably; others see them clearly as different concepts. In this theoretical overview paper, we have first of all outlined our understanding of these individual terms. We suggest how the five principles of health promotion as outlined by the World Health Organization (WHO, 1984) fit into Tannahill’s (2009) model of three overlapping areas: (a) health education; (b) prevention of ill health; and (c) health protection. Our schematic overview places health education within health promotion and health promotion itself in the center of the overarching disciplines of education and public health. We hope our representation helps reduce confusion among all those interested in our discipline, including students, educators, journalists, practitioners, policymakers, politicians, and researchers.